Individual experience affects host choice in malaria vector mosquitoes - Amélie Vantaux; Thierry Lefèvre; Kounbrobr Roch Dabiré; Anna Cohuet (Parasites & Vectors, 2014)
Abstract Background Despite epidemiological importance, few studies have explored whether individual experience and learning could affect the vertebrate host choice of mosquito disease vectors. Here, we investigated whether a first successful blood meal can modulate mosquito preference during a second blood meal. Methods In no-choice situations, females of the mosquito Anopheles coluzzii, one of the primary African malaria vectors, were first allowed to feed on either human, rabbit or guinea pig. Four days later in dual-choice situations, the same mosquitoes were allowed to choose between the two uncommon hosts, rabbit and guinea pig, as a source of blood. ELISA assays were then used to determine which host mosquitoes fed on. Results Our results indicate that, overall, mosquitoes preferred to feed on rabbit over guinea pig and that the nature of the first blood meal had a significant impact on the mosquito host choice during the second blood meal. Compared to mosquitoes that previously fed on guinea pigs or humans, mosquitoes that fed on rabbits were less likely to choose this host species during a second exposition. The decreased preference for rabbit was observed four days after mosquitoes were first exposed to this host, suggesting that the effect lasts at least the duration of a gonotrophic cycle. Furthermore, this effect was observed after only one successful blood meal. Fitness measurements on mosquitoes fed on the three different vertebrate hosts showed that the origin of the blood meal affected mosquito longevity but not fecundity. In particular, human-fed mosquitoes lived longer than guinea pig-fed or rabbit-fed mosquitoes. Conclusions Our study demonstrates that individual experience affects host choice in this mosquito species and might have strong repercussions on biting patterns in natural conditions and hence on malaria transmission.